Assessment of diffusion-weighted MRI and 18F-fluorodeoxyglucose PET/CT in monitoring early response to neoadjuvant chemotherapy in adenocarcinoma of the esophagogastric junction - Weber, Marc-André; Bender, Karen; Gall, Carl Christian Andreas von; Stange, Annika; Grünberg, Katharina; Ott, Katja; Haberkorn, Uwe; Kauczor, Hans-Ulrich; Zechmann, Christian (Journal of gastrointestinal and liver diseases, 2013)
Background & Aims: To prospectively assess whether changes in apparent diffusion coeficient (ADC) values or standardized uptake value (SUV) changes in 18F-fluorodeoxyglucose (FDG) PET correlate with treatment response under neoadjuvant chemotherapy in patients with locally advanced adenocarcinoma of the esophagogastric junction (AEG).Methods: Fifteen patients (median age, 64 years) with histologically proven AEG type I and II received 1.5 Tesla MRI including diffusion-weighted imaging and FDG PET/CT before and 14 days after neoadjuvant EOX chemotherapy. The FDG uptake of the tumor was quantified by calculating the SUV in static PET scans. ADC values within the tumor tissue were quantitatively assessed using a region-of-interest analysis excluding necrotic areas. Early metabolic response was defined as a decrease in the SUVmean≥ 35% in FDG PET two weeks following the start of neoadjuvant chemotherapy, which had been reported to be predictive of histopathological response and survival. Concordance between ADC and SUV changes, differences at first examination and overall survival were assessed.Results: The ADC within the AEG tumors was significantly lower than in normal esophagus and increased following neoadjuvant chemotherapy by 16.0±21.1% (p=0.007). Tumor glucose SUV decreased by 29.1±23.2% (p=0.002). Initial ADC and SUV were comparable in both groups (p=0.65, p=0.82). ADC increase and metabolic PET-response were concordant in 73.3% of all patients. The median overall survival was 757 days for PET-responders and 623 days for PET-non-responders (p=0.138).Conclusion: The ADC increase in AEG tumors following chemotherapy is concordant in the majority of cases to PET-response, but not correlated to prognosis in this study.Abbreviations : ADC: apparent diffusion coeficient; AEG: adenocarcinoma of the esophagogastric junction; Bq: Becquerel; DWI: diffusion-weighted imaging; EOX: Epirubicin, Oxaliplatin, Capecitabin (XelodaR); FDG: 18F-fluorodeoxyglucose; HASTE: Half-Fourier-Acquisition Single-Shot Turbo-Spin-Echo; KeV: kiloelectron volt; mAs: milliampere-second; MBq: Megabecquerel; SUV: standardized uptake value; PET: positron emission tomography; RECIST: Response Evaluation Criteria in Solid Tumors; ROI: region-of-interest; RT: radiotherapy; SPACE: Sampling-Perfection with Application-optimized Contrasts using different flip-angle Evolution; VIBE: Volumetric-Interpolated Breath-hold Examination
Gesehen am 04.10.2021
Im Titel ist die Zahl 18 hochgestellt